Protein C Deficiency Caused by a Novel Mutation in the PROC Gene in an Infant with Delayed Onset Purpura Fulminans - Mariam S. Al Harbi; Ayman W. El-Hattab (Case Reports in Dermatological Medicine, 2017)
Protein C is an anticoagulant that is encoded by the PROC gene. Protein C deficiency (PCD) is inherited in an autosomal dominant or recessive pattern. Autosomal dominant PCD is caused by monoallelic mutations in PROC and often presents with venous thromboembolism. On the other hand, biallelic PROC mutations lead to autosomal recessive PCD which is a more severe disease that typically presents in neonates as purpura fulminans. In this report, we describe an 8-month-old infant with autosomal recessive PCD who presented with multiple lumps on his lower extremities at the age of 2 months and later developed purpura fulminans after obtaining a muscle biopsy from the thigh at the age of 5 months. Protein C level was less than 10% and PROC gene sequencing identified a novel homozygous missense mutation, c.1198G>A (p.Gly400Ser). Autosomal recessive PCD typically presents with neonatal purpura fulminans which is often fatal if not recognized and treated early. Therefore, early recognition is critical in preventing morbidity and mortality associated with autosomal recessive PCD.